Information services : prospects and strategies for the Caribbean : draft paper - Gumbs, Barbara (1986)
Gives overview of the informatics activities in the Caribbean. Discusses potential information services that can be developed in the Caribbean viz. the production of software packages, data entry services, and the development of national and regional databases. Outlines the characteristics of information services and details the infrastructural arrangements that need to be put in place so that these services can be developed and maintained viz. `clean' regular supply of electricity; availability of telecommunication facilities; skilled manpower resources and high percentage of trained informaticians.